Motion Patterns Under Multiple Constraints and Master–Slave Control of a Serial Modular Biomimetic Robot with 3-DOF Hydraulic Muscle-Driven Continuum Segments - Yunrui Jia; Zengmeng Zhang; Junhao Guo; Yong Yang; Yongjun Gong (Biomimetics)
Soft modular biomimetic robots, driven by flexible actuators, are extensively used in various fields due to their excellent flexibility, environmental adaptability, and isomorphism. However, existing flexible modules typically possess no more than two degrees of freedom for structural limitations. In this study, a three-degree-of-freedom biomimetic segment driven by water hydraulic artificial muscles (WHAMs) and supported by springs was proposed, achieving integrated and modular design. The continuum robot composed of this segment can execute earthworm-, snake-, and elephant trunk-biomimetic motion modes based on operational environmental constraints. During long-distance operational tasks, distinct segments of the continuum robot can adopt varying biomimetic configurations to meet specific requirements. The closed-loop control characteristic tests were conducted on a single segment to evaluate its motion characteristics. The isomorphic master controller was designed based on the motion range of a single segment, with the maximum bending angle deviation between the master controller and biomimetic segment not exceeding 4°, and the system demonstrating favorable stability.